2012
DOI: 10.1093/mp/sss068
|View full text |Cite
|
Sign up to set email alerts
|

OsDMI3 Is a Novel Component of Abscisic Acid Signaling in the Induction of Antioxidant Defense in Leaves of Rice

Abstract: Ca(2+) and calmodulin (CaM) have been shown to play an important role in abscisic acid (ABA)-induced antioxidant defense. However, it is unknown whether Ca(2+)/CaM-dependent protein kinase (CCaMK) is involved in the process. In the present study, the role of rice CCaMK, OsDMI3, in ABA-induced antioxidant defense was investigated in leaves of rice (Oryza sativa) plants. Treatments with ABA, H(2)O(2), and polyethylene glycol (PEG) induced the expression of OsDMI3 and the activity of OsDMI3, and H(2)O(2) is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
85
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(92 citation statements)
references
References 69 publications
6
85
0
1
Order By: Relevance
“…Tobacco (Nicotiana tabacum) CCaMK was indicated to play a role in controlling the development of anther (Poovaiah et al, 1999), and pea (Pisum sativum) CCaMK was up-regulated in roots in response to low temperature and salt treatment (Pandey et al, 2002). Recent results showed that CCaMK from maize (Zea mays; ZmCCaMK) and rice (OsCCaMK) both play important roles in abscisic acid-induced antioxidant protection (Ma et al, 2012;Shi et al, 2012). Together, these results suggest that CCaMK acts as a multifunctional regulatory protein in plants.…”
Section: +mentioning
confidence: 99%
“…Tobacco (Nicotiana tabacum) CCaMK was indicated to play a role in controlling the development of anther (Poovaiah et al, 1999), and pea (Pisum sativum) CCaMK was up-regulated in roots in response to low temperature and salt treatment (Pandey et al, 2002). Recent results showed that CCaMK from maize (Zea mays; ZmCCaMK) and rice (OsCCaMK) both play important roles in abscisic acid-induced antioxidant protection (Ma et al, 2012;Shi et al, 2012). Together, these results suggest that CCaMK acts as a multifunctional regulatory protein in plants.…”
Section: +mentioning
confidence: 99%
“…Recently, a growing body of evidence reveals additional functions of CCaMK, such as response to ABA signaling and stress tolerance in wheat, maize, and rice Shi et al, 2012;Yang et al, 2011a). Hence, it is getting increasingly important to identify the downstream targets of CCaMK in order to understand the physiological role of CCaMK in different biological processes.…”
Section: Discussionmentioning
confidence: 99%
“…For the oxidative damage analysis, 4-week-old seedlings were treated with 20% PEG for 12 h. The content of MDA and the percentage of electrolyte leakage were determined as described by Shi et al (2012).…”
Section: Phenotype and Oxidative Damage Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, OsDMI3 has been found to be involved in ABA signaling in rice, where ABA treatment induced the expression of OsDMI3 and OsMPK1 as well as the activities of OsDMI3 is increased. It was also found that OsDMI3 functions upstream to OsMPK1 in regulating the activities of antioxidant enzymes and the production of H 2 O 2 in rice (Shi et al 2012(Shi et al , 2014. In maize, ZmCCaMK was identifi ed to be essential for ABAinduced antioxidant defense ( Ma et al 2012a ).…”
Section: +mentioning
confidence: 99%